2021
DOI: 10.3389/fcell.2021.697947
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Expressional Landscape of the Human Placental miRNome and Transcriptome

Abstract: Placenta is a unique organ that serves its own function, and contributes to maternal gestational adaptation and fetal development. Coordination of its transcriptome to satisfy all the maternal-fetal needs across gestation is not fully understood. MicroRNAs are powerful transcriptome modulators capable to adjust rapidly the expression level and dynamics of large gene sets. This MiR-Seq based study presents a multi-omics investigation of the human placental miRNome and its synergy with the transcriptome. The ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 61 publications
3
23
0
Order By: Relevance
“…The results showed that in RPL patients, 2 miRNAs (miR-145-5p and miR-493-5p) were upregulated, and 2 miRNAs (miR-1285-3p and miR-766-5p) were downregulated. Our review of the literature revealed that these miRNAs, which had been Frontiers in Physiology frontiersin.org replicated in more than one study, were expressed in the placenta (Lv et al, 2019;Inno et al, 2021;Smith et al, 2021). The four potential biomarker miRNAs identified in our study have never been linked to RPL before.…”
Section: Discussionsupporting
confidence: 51%
“…The results showed that in RPL patients, 2 miRNAs (miR-145-5p and miR-493-5p) were upregulated, and 2 miRNAs (miR-1285-3p and miR-766-5p) were downregulated. Our review of the literature revealed that these miRNAs, which had been Frontiers in Physiology frontiersin.org replicated in more than one study, were expressed in the placenta (Lv et al, 2019;Inno et al, 2021;Smith et al, 2021). The four potential biomarker miRNAs identified in our study have never been linked to RPL before.…”
Section: Discussionsupporting
confidence: 51%
“…It is located on chromosome 14q32 at the imprinted DLK1-DIO3 domain (mouse distal chromosome 12 domain cluster) where it can be expressed from the maternally inherited chromosome 14 (Seitz et al, 2004;Glazov et al, 2008;Morales-Prieto et al, 2013;Welten et al, 2014). Although many C14MC members appear to have variable expression patterns in the first trimester, the majority of them are expressed at a higher level in the second trimester than in other gestational stages (Morales-Prieto et al, 2012;Gu Y. et al, 2013;Gonzalez et al, 2021;Inno et al, 2021;Smith et al, 2021). Also, many C14MC miRNAs are detected in both fetal and maternal plasma in normal pregnancy (Paquette et al, 2018).…”
Section: Chromosome 14 Mirna Clustermentioning
confidence: 99%
“…Studies of miR-125b-5p expression in pregnancy complications vary based on the type and onset of these disorders. In preeclamptic placentas, one study reported that miR-125b-5p is upregulated in severe EOPE placentas ( Yang et al, 2016 ) while another one showed downregulated miR-125b-5p in LOPE ( Simsek et al, 2022 ), and a third study reported no difference ( Inno et al, 2021 ). However, miR-125b-5p was consistently shown to be upregulated in umbilical cord blood ( Simsek et al, 2022 ) and in serum of women affected by EOPE ( Yang et al, 2016 ; Tang et al, 2021 ; Simsek et al, 2022 ).…”
Section: Microrna Regulation Of Trophoblast Invasion Spiral Artery Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…Research indicates that miRNAs play key roles in physiological and pathological embryo implantation and development, and as such could represent diagnostic and therapeutic targets in pregnancy-related disorders [ 20 , 21 ]. The miRNAs secreted by human embryos could serve as biomarkers in assisted reproductive technology [ 22 ], and evidence suggests that the expression profiles of miRNA in blastocoel fluid affect blastocyst quality [ 23 ].…”
Section: Introductionmentioning
confidence: 99%